Questions & Answers

Question

Answers

Answer

Verified

92.4k+ views

We are given an inequality in this question.

$ \Rightarrow 4x - 2 > 6x + 8$ …. (Given)

Step 1: Bring the terms containing the variables on one side.

$ \Rightarrow - 2 > 6x - 4x + 8$

Step 2: Simplify the equation.

$ \Rightarrow - 2 > 2x + 8$

Step 3: Now, shift the constant to the other side, leaving the variable on one side.

$ \Rightarrow - 2 - 8 > 2x$

Step 4: Simplify the equation.

$ \Rightarrow - 10 > 2x$

$ \Rightarrow \dfrac{{ - 10}}{2} > x$

Hence, $x < - 5$.

Therefore, we have the upper limit of the variable x.

$ \Rightarrow 4x - 2 > 6x + 8$

Subtract $8$ on both the sides,

$ \Rightarrow 4x - 2 - 8 > 6x + 8 - 8$

On simplifying, we will get,

$ \Rightarrow 4x - 10 > 6x$

Now, subtract $4x$ on both the sides,

$ \Rightarrow 4x - 4x - 10 > 6x - 4x$

On simplifying, we will get,

$ \Rightarrow - 10 > 2x$

Dividing both the sides by $2$,

$ \Rightarrow \dfrac{{ - 10}}{2} > \dfrac{{2x}}{2}$

On simplifying, we will get,

$ \Rightarrow - 5 > x$

Hence, in this way, we could find the desired value without shifting. But, always remember this that when you change the sign on both the sides, the sign of inequality also changes.

Students Also Read